The effect of temperature on growth of mullet (Mugil dussumieri Val.,) Seabass (Lates calcarifer [Bloch]) and spine foot (Siganus virgatus Cuv. & Val.) - Apichart Termvidchakorn (Chulalongkorn University, 1977)
93 pages